Optimisation of hysteretic losses in high-temperature superconducting wires - Krüger, Philipp (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2014)
Hysteretic loss optimisations through numerical simulation and subsequent experimental confirmation in transport current and background field measurements: ferromagnetic shielding and topological geometry optimisation is used to reduce energy dissipation in HTS coated conductor geometries. Single tapes and coil geometries are investigated. A 3D model capable of taking into account contact resistances is also presented for the Twisted Stacked Tape Conductor cable.